2021
DOI: 10.1101/2021.01.31.428851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of re-purposed drugs that slow SARS-CoV-2 replication in human cells

Abstract: Background: The SARS-CoV-2 virus has caused the death of over 2 million people worldwide during the COVID-19 pandemic. Whilst effective vaccines have been developed and vaccination schedules are being rolled out, the identification of safe and inexpensive drugs to slow the replication of SARS-CoV-2 could help thousands of people worldwide whilst awaiting vaccination. Methods: Using SARS-CoV-2 tagged with nano-luciferase (SARS-CoV-2-ΔOrf7a-NLuc) we screened a variety of cells under optimised cell culture condit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…In vitro screening of 30 approved medicines reveals that Ebastine displayed a strong inhibition of the SARS-CoV-2 main protease (Mpro) in infected cells [24]. In addition, a preprint paper reported the ability of this in slowing the replication process of SARS-CoV-2 in human cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro screening of 30 approved medicines reveals that Ebastine displayed a strong inhibition of the SARS-CoV-2 main protease (Mpro) in infected cells [24]. In addition, a preprint paper reported the ability of this in slowing the replication process of SARS-CoV-2 in human cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that SARS-CoV2 was able to infect A549 epithelial cells., but showed limited replicative capacity. Increased NLuc signal, indicating viral replication (29), was detected when monolayers were exposed to Af culture filtrates from Af293 but not A1160 strains (P < 0.05) (Figure 2c) . Interestingly, heightened NLuc activity was detected when A549 cells were co-cultured with THP1 monocytes and Af293 culture filtrates (Supplementary Figure 2b) .…”
Section: Importancementioning
confidence: 97%
“…Equivalent quantities were used in the staining mix and fluorescence for this dye was acquired in Channel 5 of the IFC. Live-cell imaging and analyses of fungal uptake and intracellular killing were performed as described in (13) (29). NLuc activity was measured at 72 h post-infection in the presence of 0.5 L of coelenterazine as previously reported (29).…”
Section: Effect Of Viral Mimic On Antifungal Aec Responsesmentioning
confidence: 99%
See 2 more Smart Citations